The 2018 Revision of Italian Dietary Guidelines: Development Process, Novelties, Main Recommendations, and Policy Implications - Rossi, Laura; Berni Canani, Sibilla; Censi, Laura; Gennaro, Laura; Leclercq, Catherine; Scognamiglio, Umberto; Sette, Stefania; Ghiselli, Andrea (Frontiers in Nutrition, 2022)
The fourth edition of the Italian Dietary Guidelines (IDGs) for Healthy Eating was published in 2019. The objectives of the present paper were to describe the process of development of IDGs, the main recommendations, the differences with previous revisions, the concordance and differences with international guidance on a healthy diet. A National Commission oversaw IDGs development. A Scientific Dossier including analysis on nutrition, health, and risk factors status in Italy was the reference for IDGs preparation. The IDGs are based on the principles of the Mediterranean Diet and are mainly aimed to prevent obesity and nutrition-related non-communicable diseases. IDGs included 13 directives that were divided into 4 conceptual blocks: i) how to balance weight; ii) foods to be promoted; iii) foods to be limited; iv) how to ensure a varied and sustainable diet. Each directive has a box summarizing the key recommendations and lists myths and false beliefs to be dispelled. The topics of sustainability and the correct approach to food supplementation and losing weight diet were introduced in the present edition of IDGs. This paper contributes to the debate on the complexity of derivation of Dietary Guidelines and their adaptation to the national context.